2004
DOI: 10.1074/jbc.m402754200
|View full text |Cite
|
Sign up to set email alerts
|

Association of the Breast Cancer Protein MLN51 with the Exon Junction Complex via Its Speckle Localizer and RNA Binding Module

Abstract: MLN51 is a nucleocytoplasmic shuttling protein that is overexpressed in breast cancer. The function of MLN51 in mammals remains elusive. Its fly homolog, named barentsz, as well as the proteins mago nashi and tsunagi have been shown to be required for proper oskar mRNA localization to the posterior pole of the oocyte. Magoh and Y14, the human homologs of mago nashi and tsunagi, are core components of the exon junction complex (EJC). The EJC is assembled on spliced mRNAs and plays important roles in post-splici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
110
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 53 publications
3
110
0
Order By: Relevance
“…Then the prebound MLN51 may join in to form the stable core of the EJC, which in turn can interact with other mRNA-binding proteins that may be already preloaded onto the mRNA, such as Upf3b/3a, to establish a specific mRNP architecture. MLN51 interacts with the EJC component Magoh in a partially RNase-sensitive manner (24). We found that, in the absence of eIF4A3, loading of MLN51 onto mRNA is only slightly reduced, but not abolished, in contrast to loading of Y14/Magoh, which is strongly inhibited.…”
Section: Recruitment Of Ejc Core Components Onto Mrna and Ejc Assemblymentioning
confidence: 71%
See 1 more Smart Citation
“…Then the prebound MLN51 may join in to form the stable core of the EJC, which in turn can interact with other mRNA-binding proteins that may be already preloaded onto the mRNA, such as Upf3b/3a, to establish a specific mRNP architecture. MLN51 interacts with the EJC component Magoh in a partially RNase-sensitive manner (24). We found that, in the absence of eIF4A3, loading of MLN51 onto mRNA is only slightly reduced, but not abolished, in contrast to loading of Y14/Magoh, which is strongly inhibited.…”
Section: Recruitment Of Ejc Core Components Onto Mrna and Ejc Assemblymentioning
confidence: 71%
“…eIF4A3 directly contacts the bound RNA in the crystal structure, but Phe-188 of SELOR stacks with an RNA base, suggesting that MLN51 enhances the overall RNA-binding affinity of the complex. Moreover, the SELOR domain by itself can bind RNA independently of splicing (24). GST-SELOR associated with mRNA and pre-mRNA in the presence or absence of eIF4A3 (Fig.…”
Section: Loading Of Other Ejc and Associated Components In The Absencmentioning
confidence: 99%
“…1-351), the SELOR domain (MLN51.S, amino acids 137-283) required for MLN51 incorporation into the EJC core (7,22), and the unstructured C-terminal half (MLN51.Ct, amino acids 352-703) implicated in the assembly of stress granules (25). Remarkably, all the truncated proteins carrying the SELOR domain were able to precipitate eIF3 (Fig.…”
Section: Mln51 Protein Level Modulates the Translation Efficiency In mentioning
confidence: 99%
“…Given that the SELOR domain is necessary to assemble the EJC core stably onto mRNA (7,22), we wondered whether its interactions with EJC core and eIF3 were mutually exclusive. We tested whether eIF3 still binds MLN51 within the EJC core reconstituted in vitro (22).…”
Section: Mln51 Protein Level Modulates the Translation Efficiency In mentioning
confidence: 99%
See 1 more Smart Citation